2003
DOI: 10.1007/s00421-003-0895-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone substitution titrated to obtain IGF-I levels in the physiological range in hypopituitary adults: effects upon dynamic strength, endurance and EMG

Abstract: We studied the effects of individualised growth hormone (GH) substitution, aiming at normal insulin-like growth factor I (IGF-I) levels, on biomechanical output and surface electromyogram (EMG) of isokinetic muscle strength and endurance performance in 18 hypopituitary adults and compared with 17 matched healthy controls. The muscle function tests consisted of isokinetic contractions of the right knee extensors, from which torque and EMG were recorded. Three patients were excluded from the final analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…8,43 Furthermore, in a study by Ekman et al, 44 hypopituitary patients with the largest changes in IGF-I in response to GH replacement had better biomechanical output than patients with small changes in IGF-I. This is in line with previous observations that GH as well as IGF-I are of importance for muscle morphology, function, and metabolism.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…8,43 Furthermore, in a study by Ekman et al, 44 hypopituitary patients with the largest changes in IGF-I in response to GH replacement had better biomechanical output than patients with small changes in IGF-I. This is in line with previous observations that GH as well as IGF-I are of importance for muscle morphology, function, and metabolism.…”
Section: Discussionsupporting
confidence: 72%
“…This is in line with previous observations that GH as well as IGF-I are of importance for muscle morphology, function, and metabolism. 8,43 Furthermore, in a study by Ekman et al, 44 hypopituitary patients with the largest changes in IGF-I in response to GH replacement had better biomechanical output than patients with small changes in IGF-I. No correlation, however, was found in the present study between the change in serum IGF-I concentration and the change in any measure of muscle function.…”
Section: Discussioncontrasting
confidence: 63%
“…Adult patients with CPHD have been reported to show impairment of ventilatory function, and GH-replacement therapy can help restore it [4,11,12]. It has also been reported that GH-replacement therapy for GHD in adults results in increased maximal oxygen uptake, presumably due to increased respiratory muscle strength [13] and increased mean frequency of the surface electromyogram of the muscle fiber area in quadriceps [14]. However, only one report appears to have described severe respiratory failure requiring use of NPPV [12].…”
Section: Discussionmentioning
confidence: 99%